Member satisfaction is reviewed from the quality of service, communication, and trust in the East Java Independent Cooperative Mojokerto - Putra, Andre Praditya; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2025)
Research objectives: This study aims to test and analyze Member Satisfaction Reviewed from the Quality of Service, Communication, and Trust in the East Java Mojokerto Independent Cooperative. Design/Method/Approach: This research is a type of quantitative descriptive research. The population of this study is Employees of the East Java Independent Cooperative Mojokerto, with a sample of 40 respondents. This research was conducted using a questionnaire method distributed to East Java Independent Cooperative Employees in Mojokerto. The sampling technique uses a data analysis technique using simple random sampling, and the data analysis technique uses a classical assumption test and a multiple linear regression test. Research Findings: The results of this study prove that the Competence of Service, Communication, and Trust simultaneously affects the satisfaction of members of the East Java Mojokerto Independent Cooperative Theoretical contribution/originality: Simultaneous measurement of variable quality of service, communication, and trust in member satisfaction. Implications of Practice / Policy: It is hoped that readers will gain a deeper understanding of the quality of service, communication and trust that have an impact on member satisfaction, which will ultimately increase the competitiveness of the cooperative. Limitations of the study: The limitations in this study include several aspects. First, the scope of the research that only focuses on the members of the East Java Mojokerto Independent Cooperative can limit the generalization of the findings to other cooperatives with different characteristics. Second, data collection that relies on questionnaires and interviews may be influenced by the subjectivity of respondents, so that the results obtained may not reflect the actual conditions. Third, this study only examines member satisfaction from three variables, namely service quality, communication, and trust, without considering other factors such as product innovation, member participation, or cooperative financial stability that can also affect satisfaction. Therefore, further research with a broader scope and a more comprehensive approach is needed to provide a deeper understanding.